2014
DOI: 10.3928/01477447-20140430-63
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastoma With Secondary Aneurysmal Bone Cyst of the Capitate

Abstract: Chondroblastoma is a benign tumor that typically arises in the epiphysis of a long bone. There have been only 2 reported cases of chondroblastoma involving the capitate. This is the first report of chondroblastoma with secondary aneurysmal bone cyst involving the capitate. A 33-year-old man presented with a 3-year history of pain and swelling of the right wrist. Radiography as well as computed tomography showed a radiolucent area and no matrix calcification within the capitate. Magnetic resonance imaging revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…9 Sato et al reported on a case of chondroblastoma in the capitate with secondary aneurysmal bone cyst changes and complete resolution following curettage and bone grafting. 8 The case we present describes a recurrent capitate chondroblastoma treated successfully with repeat excision using curettage, phenol application, and bone grafting with capitohamate arthrodesis secondary to expansion of the tumor to the articular surface of capitohamate joint. The arthrodesis did not result with any deficits in wrist range of motion or grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…9 Sato et al reported on a case of chondroblastoma in the capitate with secondary aneurysmal bone cyst changes and complete resolution following curettage and bone grafting. 8 The case we present describes a recurrent capitate chondroblastoma treated successfully with repeat excision using curettage, phenol application, and bone grafting with capitohamate arthrodesis secondary to expansion of the tumor to the articular surface of capitohamate joint. The arthrodesis did not result with any deficits in wrist range of motion or grip strength.…”
Section: Discussionmentioning
confidence: 99%